Control of the T Follicular Helper–Germinal Center B-Cell Axis by CD8+ Regulatory T Cells Limits Atherosclerosis and Tertiary Lymphoid Organ Development. Issue 6 (10th February 2015) - Clement, Marc; Guedj, Kevin; Andreata, Francesco; Morvan, Marion; Bey, Laetitia; Khallou-Laschet, Jamila; Gaston, Anh-Thu; Delbosc, Sandrine; Alsac, Jean-Marc; Bruneval, Patrick; Deschildre, Catherine; Le Borgne, Marie; et al.
<x xml:space="preserve">Abstract</x> Background— The atheromodulating activity of B cells during the development of atherosclerosis is well documented, but the mechanisms by which these cells are regulated have not been investigated. Methods and Results— Here, we analyzed the contribution of Qa-1–restricted CD8+ regulatory T cells to the control of the T follicular helper–germinal center B-cell axis during atherogenesis. Genetic disruption of CD8+ regulatory T cell function in atherosclerosis-prone apolipoprotein E knockout mice resulted in overactivation of this axis in secondary lymphoid organs, led to the increased development of tertiary lymphoid organs in the aorta, and enhanced disease development. In contrast, restoring control of the T follicular helper–germinal center B-cell axis by blocking the ICOS-ICOSL pathway reduced the development of atherosclerosis and the formation of tertiary lymphoid organs. Moreover, analyses of human atherosclerotic aneurysmal arteries by flow cytometry, gene expression analysis, and immunofluorescence confirmed the presence of T follicular helper cells within tertiary lymphoid organs. Conclusions— This study is the first to demonstrate that the T follicular helper–germinal center B-cell axis is proatherogenic and that CD8+ regulatory T cells control the germinal center reaction in both secondary and tertiary lymphoid organs. Therefore, disrupting this axis represents an innovative therapeutic approach.